Pengelolaan Sampah Plastik di SD N Patalan Baru Bantul Dengan Metode Ecobrick: Penerapan Qs. Al-A’raf Ayat 56 - Ulumfadilah, Abimanyu Aulia; Al-Madyan, Nur Annisa Awaliyyah; Fathurrohman, Rizal (Alma Ata University Press, 2025)
This research was conducted because of the emergence of various concerns related to the processing of plastic waste, due to human actions that are still fond of littering. There are many verses that explain environmental education in the Qur'an, one of which is Surah Al-A'raf verse 56. Furthermore, in delivering environmental education, Islamic education is an alternative. In this case we take the waste processing method in the form of ecobricks as a solution in processing plastic waste. This research aims to; 1.) knowing what an ecobrick is 2.) Knowing the processing of plastic waste at SD N Patalan Baru 3.) Implementation of QS. Al-A'raf verse 56 regarding environmental education. The approach in this research This research approach is a qualitative approach, data obtained through literature review, in-depth interviews, participatory observation, and document analysis. Findings show that ecobricking can significantly reduce plastic waste while increasing students' while increasing students' awareness of the environment. So, Ecobricks can be a solution to the plastic waste pollution that occurs in society. In addition, the application of ecobricks also implements Q.S Al A'raf verse 56 in order to protect the environment. Because the utilization of ecobricks as an embodiment of Quranic teachings offers a practical way to promote environmental sustainability and responsible resource management. By implementing this approach, we can contribute to a healthier earth and a more sustainable future.Keyword: Ecobricks, Plastic Waste, Environmental Education, Religious Values, Elementary School.